The Influence of Voluntary Disclosure, Stock Beta, and Firms Size on Cost of Equity Capital - Yati Mulyati (Jurnal Keuangan dan Perbankan, 2017)
This study aimed to examine the effect of voluntary disclosure, stock beta, and firm size on the cost of equity capital in manufacturing companies in the period 2013-2015. This research used a purposive sampling method and analyzed by multiple regression, a total sample of 39 manufacturing companies listed in the IDX period 2013-2015. The results showed that voluntary disclosure did not affect the cost of equity disclosure, the more voluntary disclosure had not been able to decrease the occurrence of cost of equity disclosure, beta of stock variables affected the cost of equity capital, because the stock beta was an indicator to see the condition of the company’s financial health, the company had no effect on voluntary disclosure, this result showed that the size of a company’s size could not reduce the risk level.DOI: https://doi.org/10.26905/jkdp.v21i3.1506